Analisis Pengaruh Kompensasi dan Pelatihan Kerja Terhadap Produktivitas Karyawan Ajb Bumiputera 1912 - Sri Waluya; Erliza (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
In this modern era the development of science and technology more advanced, it encourages the rapid development of companies, so that the necessary changes - changes that must be done by the company. In this case the company has the support of human resources to promote the company, one of them is the employee, where the provision of compensation and job training is very influential on employee productivity, for that the author is interested to take the title